The Influence of Promotion on Consumer Purchase Decisions for Kacang Dua Kelinci Products at Alfamart Branch in Pagedangan, South Tangerang - Wahyuni, Sri (Implikasi: Jurnal Manajemen Sumber Daya Manusia, 2023)
This study aims to determine the effect of promotion on purchasing decisions for Dua Kelinci peanut products at Alfamart Pagedangan, South Tangerang Branch. The method used is explanatory research with a sample of 96 respondents. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this research variable promotion obtained an average score of 3.41 with good criteria. Purchasing decision variable obtained an average score of 3.84 with good criteria. Promotion has a significant effect on purchasing decisions with the regression equation Y = 9.688 + 0.842X, and a correlation value of 0.771 or strong with a determination of 59.5%. Hypothesis testing obtained t count > t table or (11.744 > 1.986) and also strengthened by a significance of 0.000 <0.05.